Understanding the ‘therapeutic misconception’ from the research participant’s perspective - Kim, Y. H. (Journal of medical ethics, 2016)
Dr Appelbaum's specific criticisms of our study1 rely on two general assertions with which he begins his commentary: that ‘dozens of studies’ have ‘confirmed’ the high prevalence of the therapeutic misconception (TM) and that our current study ‘exemplifies’ our group's overall research programme on TM, going so far as to attribute a non-scientific motive to our efforts. We think the readers deserve a fuller picture of the actual state of TM research as well as a more accurate picture of our overall TM research programme. Such a picture will explain why, in the current study, we used the methods we did and how we interpreted the results.First, we agree that the conventional wisdom takes it as a ‘given’ that TM is ubiquitous. But we disagree that the current evidence base supports that conventional view. Even after decades and ‘dozens’ of studies on TM, there is no widely accepted definition of TM.2 Some definitions in fact incorporate conceptual errors, such as the idea that desire for benefit is inherently an indication of TM,3 ignoring the fact that people volunteer for studies with the hope for benefit but understand perfectly well that the study's primary purpose is not to benefit them. In fact, research subjects quite often respond to interview questions intended to measure TM with answers that both support and contradict the presence of TM,3-5 making it difficult to interpret what they actually believe.6 The desire to understand and clarify this messy state of …